The results of using free osteomyofascial flaps in the simultaneous reconstruction of combined post-resection facial defects with an intraoral component - A. S. Sharapo; V. Yu. Ivashkov; А. М. Mudunov; M. V. Bolotin; M. Bektemirov; A. E. Raportinova (Опухоли головы и шеи, 2020)
The study objective is to analyze the results of the use of free osteomyofascial flaps in the reconstruction of combined post-resection facial defects with an intraoral component. Materials and methods. Fifty-three patients were operated by the proposed method. The muscle portions which were used with free flaps were: m. flexor hallucis longus with the free fibula flap (n = 27), m. vastus lateralis with anterolateral thigh flap (n = 11), m. subscapularis with the scapula free flap (n = 15). An analysis of postoperative complications was performed, as well as an analysis of the timing of dental implantation. Results. The average hospital stay was 15 days. The main complications from the recipient area were: local inflammation in the reconstruction area – 2 (3.8 %) cases, hematoma on the neck – 2 (3.8 %), fistula formation – 1 (1.9 %), full flap necrosis was noted in 1 (3.7 %) case, hypertrophic growths of granulation tissue on the muscle portions of the flaps in 3 (5.7 %). The main complications from the donor zone: hematomas – 0 cases. In 2 (13.3 %) patients after using a chimeric scapular flap, lymphorrea up to 50–70 ml was noted. Dental implantation was performed in 4 (9.5 %) cases. There were no complications or difficulties in performing dental implantation. The average time taken to form the soft tissue contour in the area of implants after installing the gingiva formers in our study was 2.5 weeks, which is 2 weeks faster than using flaps that include a skin paddle. Conclusion. This reconstruction method could be used as a main for the plastic elimination of combined facial defects with an intraoral component.